Factors Associated with Customer Satisfaction towards Customer Loyalty among Star Grade Hotels - Fernando, W.B.J.A.J (Journal of Asian Business Strategy, 2019)
The research is to find the relationships between variables namely service quality, price, customer satisfaction, customer loyalty, and the moderating impact of gender in star grade hotels in Sri Lanka. The convenience sample technique is adopted with sample size of 303. The main data collection point is Bandaranayake international airport Colombo. The online link of the questionnaire is shared with departing passengers who stayed at star grade hotels during their visit in Sri Lanka. The study findings show that a positive linear relationships between service quality and customer satisfaction, between price and customer satisfaction, and customer satisfaction and customer loyalty. Customer satisfaction is found as a mediator while gender is found as a moderator. Hoteliers should adjust their strategies so as to satisfy the customers while taking into account research findings. The future study can be conducted having an extra questionnaire for the employees of star grade hotels in order to get their perception in relation to research area.